An intensified approach for transesterification of biodiesel from Annona squamosa seed oil using ultrasound-assisted homogeneous catalysis reaction and its process optimization. (1st May 2021) - Sundaramahalingam, M.A.; Karthikumar, S.; Shyam Kumar, R.; Samuel, Karl J.; Shajahan, S.; Sivasubramanian, V.; Sivashanmugam, P.; Varalakshmi, P.; Syed, Asad; Marraiki, Najat; Elgorban, Abdallah M.; Vinoth Kumar, R.; et al.
Graphical abstract: Highlights: Annona squamosa seed oil was found as a new source for biodiesel production. Ultrasound assisted extraction of oil was assessed to extract >94% Optimized the ultrasound assisted extraction and transesterification using RSM. Conversion ratio of annona squamosa seed oil to biodiesel was evaluated as >95% Abstract: In this work, Annona squamosa seed oil (ASSO) was extracted using ultrasound-assisted extraction (UAE) and converted into fatty acid methyl esters (FAME) by ultrasound-assisted transesterification (UAT) using methanol and KOH. The multivariable process of UAE and UAT was optimized using a response surface methodology (RSM). The experimental data were analyzed by Pareto analysis of variance (ANOVA) and quadratic polynomial models developed using non-linear regression analysis. A maximum ASSO yield of 31.91% was achieved by the model with the optimum conditions for UAE: liquid-to-solid ratio, 8.8 mL g −1 ; extraction temperature, 45 °C; sonication time, 19.5 min; and sonication amplitude, 88%. The maximum conversion of ASSO into biodiesel (97.6%) was achieved with the optimum condition of the model: oil-to-methanol ratio, 5.04; catalyst concentration, 1.12%; temperature, 57 °C; and sonication time, 113 min. These models were found to be significant at the 95% confidence level. The transesterified ASSO FAME was characterized using Fourier-transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), gas chromatography mass spectrometry (GC–MS), 1 H-nuclear magnetic resonance ( 1 H NMR), and fluorescence spectroscopy methods. Various physicochemical properties of ASSO and ASSO FAME were characterized according to ASTM standards. The ultrasound-assisted extraction and transesterification process was found to be rapid and simple without any change in the product quality. Importantly, ASSO was found to be a possible new source for potential biodiesel production.